Factors Influencing Consumers’ Buying Decision on Big Bike in Khon Kaen - Srisongkram, Yuphawadi; Putachote, Nitipon (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The research objectives were 1) to study decision-making behavior, 2) to compare consumers’ buying decisions by personal factors, 3) to study the importance level of the marketing mix (8Ps), and 4) to study marketing mix (8Ps) factors influencing consumers’ buying decision on a big bike in Khon Kaen. The 400 sample population was chosen by convenient selection without using probabilities. Data were collected using a questionnaire, and were analyzed using frequency, percentage, mean, standard deviation, independent t-test, One-Way ANOVA, and Multiple Regression Analysis. The research results revealed that 1) Buying decision behavior was buying with installments. It takes more than a month to make a decision. The motorcycle size was 400-800 cc, with a price from 350,001-600,000 baht. It was purchased from a dealer because of an impression of its standard and high-quality service. Buyers are influential in their purchases. The Harley-Davidson was chosen based on its looks, shapes, and buyers’ preferences. 2) The comparison of decision-making to buy a big bike classified in terms of personal factors revealed that age, status, education level, occupation, and average income had no different purchasing decisions. However, consumers with different genders had different buying decisions. 3) An emphasis is put on overall marketing mix factors (8Ps) at the highest level. People aspects, product, productivity and quality, process, marketing promotion, and price aspects were at the highest level. Physical evidence aspect and distribution channels were at a high level. 4) The marketing mix on price, product, productivity and quality, and physical evidence affected the buying decision with a statistically significant difference at .05.